I'm trying to compute the integral $$\int_{0}^{\infty}dx \, x^{2}\operatorname{sech}^{2}(x)=\frac{\pi^{2}}{12}.$$ Manually, one obtains, quite naively, $$\int dx \, x^{2}\operatorname{sech}^{2}(x)=\operatorname{Li}_{2}(-e^{-2x})-x^{2}-2x\log(e^{-2x}+1)+x^{2}\tanh(x),$$ which of course is not possible to evaluate at infinity in this form.

I was trying to turn this thing into a series, but I'm having trouble.

  • $\begingroup$ Is this somehow related to you previous question, math.stackexchange.com/questions/3217348/… where you assert that integral also has the value $\frac{\pi^2}{12}?$ $\endgroup$ – Thomas Andrews May 7 at 16:44
  • $\begingroup$ @ThomasAndrews It is related but unrelated at the same time. They appear quite differently in my treatment of a problem but both happen to yield the same value. $\endgroup$ – KernelPanic May 7 at 16:46
  • 1
    $\begingroup$ Note that it is possible to compute the limit of your indefinite integral as $x \to \infty$, since $\lim_{x \to \infty} x^2 (1 - \tanh (x)) = 0$ and $\lim_{x \to \infty} x \log(1 + \mathrm{e}^{-2x}) = 0$. Together with the lower limit this yields $- \operatorname{Li}_2 (-1) = \frac{\pi^2}{12}$ for the definite integral. $\endgroup$ – ComplexYetTrivial May 7 at 20:13

Sort of hopping off of @J.G.'s shoulders, we may evaluate $$f(s)=\int_0^\infty x^s\text{sech}^2(x) dx$$ using the same trick, namely $$f(s)=4\int_0^\infty \frac{x^s e^{-2x}dx}{(1+e^{-2x})^2}=4\sum_{n\geq1}(-1)^{n-1}n\int_0^\infty x^s e^{-2nx}dx$$ This integral is rather easy: $$\int_0^\infty x^se^{-2nx}dx=\frac{\Gamma(s+1)}{(2n)^{s+1}}$$ So $$f(s)=\frac{2^2}{2^{s+1}}\Gamma(s+1)\sum_{n\geq1}\frac{(-1)^{n-1}}{n^s}\\ f(s)= 2^{1-s}(1-2^{1-s})\Gamma(s+1)\zeta(s)$$

  • $\begingroup$ I believe you're off by a sign in that last expression. $\endgroup$ – John Barber May 8 at 2:57
  • $\begingroup$ Nice generalization. That's my kind of answer. I always like solving an infinite number of problems instead of just one. $\endgroup$ – marty cohen May 8 at 3:35
  • $\begingroup$ @martycohen I couldn't agree more :) $\endgroup$ – clathratus May 8 at 3:36

Since $\operatorname{sech}x=\frac{2e^{-x}}{1+e^{-2x}}$, your integral is $$\int_0^\infty\frac{4x^2e^{-2x}dx}{(1+e^{-2x})^2}=4\sum_{n\ge 1}(-1)^{n-1}n\int_0^\infty x^2e^{-2nx}dx=\sum_{n\ge 1}\frac{(-1)^{n-1}}{n^2}=\eta(2)=\frac{\pi^2}{12}.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.